Motor neurone disease in Lancashire and South Cumbria in North West England and an 8 year experience with enteral nutrition. (February 2016) - Chhetri, Suresh Kumar; Bradley, Belinda Fay; Majeed, Tahir; Lea, Robert William
Abstract: Motor neurone disease (MND) is a fatal neurodegenerative disease of unknown aetiology. Malnutrition is a common occurrence and an independent risk factor for worse prognosis. However, it remains unclear whether provision of enteral nutrition (EN) through a gastrostomy tube offers any survival advantage. Our aim was to describe the demographic and clinical characteristics of MND in Lancashire and South Cumbria in North West England and the impact of EN on survival in the 8 year period of 2005–2012. Four hundred and seven patients with MND were identified through the Preston MND care and research centre registry giving a crude incidence rate of 3.15/100, 000. Three hundred and forty patients with adequate information were included in the final analysis of whom 53.2% were male. The presentation was limb/spinal in 62.1% and bulbar in 37.9% of patients, bulbar onset being more common in elderly females. Mean age of onset was 67.28 years (standard deviation 11.06; range 22.78–93.06). Median survival was 1.98 years (range 1.18–3.05). Ninety-one patients received EN of whom 67% had bulbar onset disease. EN was not associated with a statistically significant survival advantage except for the subgroup who received EN more than 500 days after symptom onset. In conclusion, the early requirement for EN may indicate a prognostically less favourable subgroup.